A SURVEY ON GENDER DIFFERENCES IN LANGUAGE CHOICE OF COASTAL KONJO COMMUNITY - Ningsih, Sri; Firdaussy, Uus Faizal; Rusata, Tatang (Jurnal Masyarakat dan Budaya, 2023)
Community language usage patterns are often fundamental to minority language maintenance. This study investigates the gender differences in language choice within the Coastal Konjo residing in South Sulawesi Province and explores the implications of its language maintenance. The contexts of language use are varied based on the speaker’s role, the topic of conversation, and the situation of the conversation to understand how gender influences language use and transmission practices. A survey method is used to gather information from 80 respondents, and SPSS is used for descriptive and inferential statistical analysis. Descriptive analysis shows that the Konjo language is the most widely spoken, followed by Bahasa Indonesia, Buginese, and mixed-use languages. The inferential statistical analysis also shows that there are no appreciable gender disparities in the Coastal Konjo community’s language choice (p > 0.005) in each context. However, the data reveals a distinct difference in how the Buginese is used, with females appearing to utilize it more frequently than males. This suggests that females have more language contact with Buginese who have long coexisted with coastal Konjo speakers in Bulukumba. Moreover, the findings indicate that males are more crucial to the maintenance of the Konjo language than females.